Pengaruh Kompetensi Terhadap Kinerja Pegawai di Lingkungan Inspektorat Kota Cimahi - Hidayat, Fajar; Kushendar, Deden Hadi; Mulawarman, Aditia (Universitas Batanghari Jambi, 2024)
The city of Cimahi is a small city when compared to several other cities in Indonesia, especially in West Java, but has a variety of interesting things, so it is called campernik. Currently, the City of Cimahi is not only burdened by the dense population and its demographic characteristics and diversity which have implications for the presence of urban problems, but also by the high demand for health, education, infrastructure and other general urban problems such as sanitation and unemployment. This problem is of course a shared responsibility, especially regional apparatus such as offices, agencies, sub-districts and sub-districts in Cimahi City according to their respective work areas. In the framework of administering the government, regional apparatuses become local government organizations that have responsibility to the Mayor of Cimahi with the assistance of supervision by the Inspectorate through the Regional Secretary. Quantitative methods were used in this study with a population and sample of 34 employees in the Cimahi City Inspectorate. The type of data used is primary data obtained through distributing questionnaires to all employees. The results of this study are that there is a significant influence between competency and employee performance variables in the Cimahi City Inspectorate environment of 97.7%. This shows that the better the competence of employees in the agency, the performance of employees will also increase.